2018
DOI: 10.1016/j.jpsychires.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness, brain metabolic activity, and in vivo amyloid deposition in asymptomatic, middle-aged offspring of patients with late-onset Alzheimer's disease

Abstract: The natural history of preclinical late-onset Alzheimer´s disease (LOAD) remains obscure and has received less attention than that of early-onset AD (EOAD), in spite of accounting for more than 99% of cases of AD. With the purpose of detecting early structural and functional traits associated with the disorder, we sought to characterize cortical thickness and subcortical grey matter volume, cerebral metabolism, and amyloid deposition in persons at risk for LOAD in comparison with a similar group without family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
4
16
1
Order By: Relevance
“…The association between amyloid positivity and HVL in our cohort was at the level of a trend or was even nonsignificant depending on the regression models used. These observations are consistent with previous contributions indicating that amyloid burden may affect hippocampal integrity only in some vulnerable individuals, thereby accounting for a small percentage of HVL [42][43][44]. Our data parallel those in previous reports pointing to the relative independence between amyloid pathology and hippocampal structural changes in preclinical and prodromal AD cases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The association between amyloid positivity and HVL in our cohort was at the level of a trend or was even nonsignificant depending on the regression models used. These observations are consistent with previous contributions indicating that amyloid burden may affect hippocampal integrity only in some vulnerable individuals, thereby accounting for a small percentage of HVL [42][43][44]. Our data parallel those in previous reports pointing to the relative independence between amyloid pathology and hippocampal structural changes in preclinical and prodromal AD cases.…”
Section: Discussionsupporting
confidence: 93%
“…HVL is known to be highly variable in the course of normal brain aging [41]. Consistent with recent contributions [42][43][44][45], the mean HVL in this series (4.5 years after inclusion) varied from 1 to 2.5%. The proportion of HVL in our series is slightly lower than the recent observations by Nobis et al [46], who published normative data from 19,700 UK Biobank cases and reported an acceleration of HVL after the age of 60 years with a 3.5% reduction between 70 and 75 years of age.…”
Section: Discussionsupporting
confidence: 86%
“…Whether amyloid load impacts on hippocampal volumes in cognitively preserved individuals is still matter of debate. Previous studies implied that this could be the case only in some vulnerable individuals (Nosheny et al, 2015; Khan et al, 2017; Duarte-Abritta et al, 2018). Equally ambiguous is the association between DTI parameters and amyloid load in normal aging.…”
Section: Discussionmentioning
confidence: 97%
“…Family history increases the risk of developing LOAD (Bertram et al, 2010;Mosconi et al, 2010), and is second only to high age as an epidemiological risk factor. As published previously, persons who are at risk of developing LOAD because of their family history, which can be in part demonstrated by possession of the apolipoprotein E (APOE) ε4 allele, show altered functional and anatomical connectivities (Bendlin et al, 2010;Sánchez et al, 2017;Sheline and Raichle, 2013;Sheng et al, 2017), changes in cognitive variables (Abulafia et al, 2018;Ballard and O'Sullivan, 2013;Loewenstein et al, 2016;Rapp and Reischies, 2005;Reinvang et al, 2012), and abnormal brain structure (Duarte-Abritta et al, 2018;During et al, 2011;Mosconi et al, 2014Mosconi et al, , 2013Reiman et al, 2005). In particular, we observed in a sample of offspring of LOAD patients (O-LOAD) that functional connectivity was related to subtle cognitive alterations in episodic memory and the capacity to recover from semantic interference effects during learning when compared to healthy control subjects (CS) (Sánchez et al, 2017).…”
Section: Introductionmentioning
confidence: 94%